2018
DOI: 10.1007/s10803-018-3700-0
|View full text |Cite
|
Sign up to set email alerts
|

Mock Juror Perceptions of Child Witnesses on the Autism Spectrum: The Impact of Providing Diagnostic Labels and Information About Autism

Abstract: Research suggests that autistic children can provide accurate and forensically useful eyewitness evidence. However, members of a jury also rely on non-verbal behaviours when judging the credibility of a witness, and this could determine the verdict of a case. We presented mock jurors with videos (from an experimental study) of one of two child witnesses on the autism spectrum being interviewed about a mock minor crime. Results demonstrated that providing jurors with generic information about autism and/or info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 44 publications
(56 reference statements)
1
17
0
Order By: Relevance
“…The present findings that the provision of an ASD label together with background information about the disorder resulted in more positive likeability and honesty perceptions of an autistic defendant is in line with previous findings in everyday contexts as well as for child witnesses (Brosnan and Mills 2016; Crane et al 2018; Matthews et al 2015; Sasson and Morrison 2017; Sasson et al 2017). In contrast, the defendant’s lack of remorse troubled many participants in the No label condition who took it to imply that he was disinterested, uncaring, and did not regret his actions, which reduced his overall likeability.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present findings that the provision of an ASD label together with background information about the disorder resulted in more positive likeability and honesty perceptions of an autistic defendant is in line with previous findings in everyday contexts as well as for child witnesses (Brosnan and Mills 2016; Crane et al 2018; Matthews et al 2015; Sasson and Morrison 2017; Sasson et al 2017). In contrast, the defendant’s lack of remorse troubled many participants in the No label condition who took it to imply that he was disinterested, uncaring, and did not regret his actions, which reduced his overall likeability.…”
Section: Discussionsupporting
confidence: 92%
“…However, knowledge and attitudes about ASD have improved in recent years (Dillenburger et al 2013; White et al 2016), and in turn knowledge has been shown to decrease stigma (Gillespie-Lynch et al 2015). Recently, Crane et al (2018) reported that providing a diagnosis label alongside further generic information about ASD resulted in more positive credibility ratings of an autistic child witness. Interestingly, however, this effect was not observed for a second autistic child witness who displayed fewer atypical behaviours, highlighting the impact of heterogeneity in the presentation of autistic behaviours and potentially a need for tailored, individualised information about how ASD affects that particular person.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While recall was coded for completeness and accuracy, narrative coherence was not assessed. Thus, it is unclear whether WAFA interviews improved the ability of autistic witnesses to provide more coherent and relevant narrativeswhich is an important avenue for future research given the substantial evidence of differences in narrative ability in ASD, which in turn may impact perceptions of credibility (e.g., Crane et al, 2018). It is also important to note that the present study utilised a relatively short delay of around 30 minutes; in real life, it is unlikely that a witness would receive a formal investigative interview this soon after witnessing a crime.…”
Section: Discussionmentioning
confidence: 99%
“…Further research is required to understand how diagnostic disclosure can lead to more consistent and sustained positive effects on social perception and behavior. In particular, the relationship between autism knowledge and the psychological effects of disclosing a diagnosis of autism is receiving increasing attention (Gillespie-Lynch et al, 2015; Sasson and Morrison, 2017; Crane et al, 2018). It is possible that such effects may be associated with increased self-awareness of one’s own taken-for-granted assumptions toward others with a diagnosis, which raises the question as to whether knowledge of the effects of a helping bias could potentially serve to correct the effects of such a bias?…”
Section: Discussionmentioning
confidence: 99%